PEMENUHAN AKSESIBILITAS SARANA DAN PRASARANA BAGI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSIF KOTA BANJARMASIN - Alpha Ariani (Universitas Achmad Yani Banjarmasin, 2020)
Educational facilities and infrastructure is one of the important resources in supporting the learning process in schools. The research aims to know and analyze the fulfillment of the accessibility of infrastructure facilities in inclusive elementary schools of Banjarmasin City. This study uses a qualitative descriptive approach. The research was conducted in five elementary schools that provided inclusive education. Data collection techniques used interviews, observation, and documentation. Informan were the principal school, class teachers, and special teachers. The results of the research showed that all schools had complete infrastructure, but managementand maintenance were still not optimal. The accessibility of learning infrastructure and special infrastructure facilities were not yet fulfilled by inclusive schools. Cooperation from all parties is needed to complete and manage infrastructure in inclusive schools so that services and learning is more qualified.